Poor sleep quality remains a major challenge among tertiary education students in Ghana: A cross-sectional study in a Ghanaian University - David Larbi Simpong; Ansumana Bockarie; Akosua Bema Kumah; Alex Bismark Atta-Owusu; Mordecai Eshun; Bernice Akua Frimpong; Beatrice Bachella; George Nkrumah Osei (IBRO Neuroscience Reports)
Introduction: Sleep plays a crucial role in health, well-being, and academic performance. Despite the recognized importance of good sleep for students, there is a need for a deeper understanding of the sleep problems faced by university students to inform effective campus support services and interventions. This study aimed to evaluate sleep quality among university students by assessing differences in key sleep parameters between sex and age groups. Methodology: A cross-sectional study was conducted to assess sleep quality using the validated Pittsburgh Sleep Quality Index among 295 undergraduate students at the University of Cape Coast, Ghana. Demographic characteristics of age and sex were also collected. Data were analyzed using descriptive statistics, Pearson's correlation, and cross-tabulations to compare sleep quality scores between sex and age groups. Results: The study included 295 undergraduate students aged 20–29 years, of which 53.2 % were male. Overall, 48.5 % of participants exhibited poor sleep quality (PSQI >5). The distribution of global PSQI scores varied by age group, with those aged 25, 27, 28, and 29 reporting higher rates of poor sleep quality. Mean scores on global PSQI scores and other components, including sleep duration and habitual sleep efficiency, were highest among those aged 25 years. Female students were more likely to experience poor sleep quality than male students (51.4 % vs. 45.2 %). Key sleep parameters such as sleep latency, disturbances, and daytime dysfunction showed significant associations with increasing age, although the correlations were weak. Global PSQI scores significantly correlated with both age (r = 0.378, p = 0.001) and sex (r = 0.212, p = 0.001). Conclusion: This study revealed a high prevalence of poor sleep quality among the respondent, with sleep disturbances and duration disproportionately affecting their sleep quality. These findings underscore the need for universities to prioritize promoting healthy sleep habits and addressing diverse sleep component issues within their student populations.